Project ONE – External Evaluation 1ST REPORT 31 May 2023 (on behalf of CECOA) - Carvalho, X. (2023)
Project ONE - Opening adult education Networks to European cooperation (621467-EPP-1-2020-1-IT-EPPKA3-IPI-SOC-IN) aims to reinforce the quality of Adult Education (AE), contributing for social inclusion in Europe, reinforcing capacity building in existing networks in Italy, Portugal and Slovakia, through four (4) themes, such as (i) Guidance services; (ii) Reaching out and active engagement of adults in both education and validation processes; (iii) Validation of non-formal and informal learning and (iv) Soft and basic skills for inclusion and active citizenship. The project uses the European Peer Review Methodology (EPRM) and is a multi-stakeholder partnership, involving organizations and public authorities from the three (3) project countries. The external evaluation of Project ONE is developed within the Impact Assessment strategy defined in the project proposal, that combines internal and external evaluation.